Characterization of the genes for the hexagonally arranged surface layer proteins in protein-producing Bacillus brevis 47: complete nucleotide sequence of the middle wall protein gene. - Tsuboi, A (1988)
Bacillus brevis 47 contains two surface (S)-layer proteins, termed the outer wall protein (OWP) and the middle wall protein (MWP), which form a hexagonal array in the cell wall. The MWP and OWP genes are contained in the 9-kilobase-pair (kbp) BclI fragment and constitute an operon under coordinate control of their expression. The nucleotide sequence of a 3.8-kbp EcoRI-SacI fragment containing the entire MWP gene has been determined in this study. Together with the DNA sequence of the promoter region for the MWP-OWP gene operon (H. Yamagata, T. Adachi, A. Tsuboi, M. Takao, T. Sasaki, N. Tsukagoshi, and S. Udaka, J. Bacteriol. 169:1239-1245, 1987) and that of the OWP gene (A. Tsuboi, R. Uchihi, R. Tabata, Y. Takahashi, H. Hashiba, T. Sasaki, H. Yamagata, N. Tsukagoshi, and S. Udaka, J. Bacteriol. 168:365-373, 1986), the complete nucleotide sequence of the MWP-OWP gene operon has been determined. The MWP gene encodes a secretory precursor of the MWP, consisting of a total of 1,053 amino acid residues with a signal peptide of 23 amino acid residues at its amino-terminal end. Bacillus subtilis harboring the MWP gene synthesized an immunoreactive polypeptide with almost the same molecular weight as the authentic MWP, as judged by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The amino acid compositions deduced from the MWP and OWP genes were similar to the chemical amino acid compositions of other S-layer proteins in the predominance of acidic amino acids compared with basic amino acids and in the very low content of sulfur-containing amino acids. The acidic nature of the MWP and OWP was confirmed by isoelectric focusing on polyacrylamide gels. In addition, circular dichroism spectra indicated that the S-layer proteins in B. brevis 47 were composed of approximately 30% beta-sheet and 5% alpha-helical structures, with the remainder of the polypeptide backbone being aperiodic in nature.